PERKEMBANGAN PEMIKIRAN HUKUM DALAM MUHAMMADIYAH - Dian Berkah (Jurnal Hukum Islam, 2012)
This paper is studying development of legal though engendered by Majlis Tarjih Muhammadiyah. Development of human interaction is very balance with the need of law as human control. However, it has unbalance relation with the law product which is produced. Therefore, it should produce the new law product as a human life foundation which has not been punished explicitly in al-Quran and al-Hadits. This matter needs concrete action in looking for new law from both sources of Moslem which are called ijtihad. This action is developed widely by social-religious organization such as Muhammadiyah. Furthermore this organization established Majlis Tarjih in 1927 as a place for ijtihad which is grown till now. In its actions, Muhammadiyah has made several law-thinking which follow the methods development of ijtihad, branding, and also it is not far from the recent situation and condition.